On-Body Characterization of Planar Differential Antennas for Multiple, Wide, and Narrow Bands - Luigi Vallozzi; Domenico Pepe; Thijs Castel; Hendrik Rogier; Domenico Zito (International Journal of Antennas and Propagation)
This paper reports the results of the on-body experimental tests of a set of four planar differential antennas, originated by design variations of radiating elements with the same shape and characterized by the potential for covering wide and narrow bands. All the antenna designs have been implemented on low-cost FR4 substrate and characterized experimentally through on-body measurements. The results show the impact of the proximity to the human body on antenna performance and the opportunities in terms of potential coverage of wide and narrow bands for future ad hoc designs and implementations through wearable substrates targeting on-body and off-body communication and sensing applications.